Žalovanje za izgubljenom aurom? Pirandellov esej 'Ilustratori, glumci i prevoditelji' - Čale, Morana (Array, 2007)
Mourning the Lost Aura? Illustratori, attori e traduttori and the Discursive Subversion of the Motherhood Metaphor Pirandello's early essays, subsequently Ťrevisedť by the author, include various self-denying, deconstructive textual signals, undermining the apparently categorical claims about the falsifying quality of representative supplements, and providing dialogical space for the conflicting views on the issue. The paper will contend that the very project of treating the problems of nature vs. culture, original vs. copy, script vs. performance, entails the complexity of the author's views on the presumed disjunction of the 'inside' and the Ťoutsideť of the text. Drawing on Derrida's understanding of parergon as a concept pertaining to the 'discourse of a limit', the paper will foreground the ambivalence of the notion of 'superfluity' recurring in Pirandello's work, and the ambiguity of the metatextual use - in essays as well as in fiction - of the biological metaphors linked to motherhood, to be illustrated by a brief examination of the reframing, transcodifications and interpretive vicissitudes in the Favola del figlio cambiato. In conclusion, an attempt will be made to demonstrate the affinities between Pirandello's theories and Benjamin's notion of the aura.